Town and Gown Differences Among the 100 Largest Medical Groups in the United States. (July 2016) - Welch, W. Pete; Bindman, Andrew B.
Abstract : Purpose: The authors undertook a study to determine whether large academic and community-based medical groups differ in terms of their financial stake in Medicare Advantage or Medicare Accountable Care Organizations (ACOs) and whether their participation in these alternative payment models is related to their size, specialty mix, and Medicare physician market share in their local area. Method: The authors used the 2013 Medicare Data on Provider Practice and Specialty database and a national database of ACOs to conduct a cross-sectional descriptive study of the 100 largest medical groups in the United States. Medical groups were categorized as academic or community based on matches of their name with a list of U.S. medical schools or the results of a series of Internet search procedures. Results: Sixty-eight of the 100 largest groups were academic, and 32 were community based. On average, community-based groups had more than twice the percentage of primary care physicians as academic groups (mean, 38.4%; 95% CI, 34.7%–42.0%; vs. 18.3%; 95% CI, 17.0%–19.6%). Community groups were significantly ( P < .001) more likely than academic groups to have a financial stake in a Medicare ACO or Medicare Advantage plan, but this difference was no longer significant when the percentage of primary care physicians in the group was added to the model. Conclusions: The specialty mix within academic medical groups may hinder their ability to transform themselves into organizations that can manage the financial responsibilities of caring for a patient population through a Medicare ACO or Medicare Advantage. Abstract : Supplemental Digital Content is available in the text.